Resolving Residential Mortgage Distress : Time to Modify? - Andritzky, Jochen (Washington, D.C. : International Monetary Fund, 2014)
In housing crises, high mortgage debt can feed a vicious circle of falling housing prices and declining consumption and incomes, leading to higher mortgage defaults and deeper recessions. In such situations, resolution policies may need to be adapted to help contain negative feedback loops while minimizing overall loan losses and moral hazard. Drawing on recent experiences from Iceland, Ireland, Spain, and the United States, this paper discusses how economic trade-offs affecting mortgage resolution differ in crises. Depending on country circumstances, the economic benefits of temporary forbearance and loan modifications for struggling households could outweigh their costs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet